A "Surprise" Health Policy Legislative Victory. Issue 6 (14th December 2021) - Hall, Mark A.
Abstract: It was a happy surprise when, overcoming partisan divisions and interest‐group lobbying, Congress enacted the No Surprises Act, which bans unfair out‐of‐network "balance billing." Although this is only a modest legislative victory, key efforts by the health policy community made a real difference in a time of legislative gridlock .